Serum migration inhibitory factor levels in periodontal health and disease, its correlation with clinical parameters - Aruna Ganganna; Anitha Subappa; Purnima Bhandari (Indian Journal of Dental Research, 2020)
Objectives: Periodontal infections are an important risk factor for systemic disease and are driven primarily by the cytokines. Migration Inhibitory Factor (MIF) is a key cytokine which mediates acute and chronic inflammation alongside, a molecular link between chronic inflammation and immune mediated conditions. Hence, the present study was carried to measure the serum MIF levels in periodontal health, disease and to correlate the levels with the clinical parameters. Material and Methods: Sixty subjects were divided into three groups (each group n = 20) based on the gingival index (GI), probing pocket depth (PPD), and clinical attachment level (CAL) as group I healthy; group II gingivitis; and group III chronic periodontitis. The serum MIF level was measured using quantitative sandwich enzyme immunoassay technique. Results: Highest level was detected in Group III with a mean of 71.8 ng/ml and the lowest in group I (6.1 ng/ml). Serum MIF levels did not correlate with the clinical parameters. Conclusion: Increased serum MIF levels in chronic periodontitis patients suggest its role as an inflammatory biomarker and may have a role in inflating the systemic inflammation. Summary: Serum Migration inhibitory factor can be used as an inflammatory marker for periodontal disease